Early arteriovenous malformation mimicking pediatric capillary malformation: diagnostic value of infrared thermography - Hao Gu; Xiaojie Yue; Xiong Zhao; Qiang Shu (Hereditas)
Abstract Early-stage arteriovenous malformations (AVMs) and port-wine stains (PWS) exhibit overlapping clinical presentations, notably as flat, irregular erythema, posing significant diagnostic challenges. Conventional imaging techniques offer insufficient resolution for microvascular assessment during initial evaluation, and definitive diagnosis requires invasive tissue biopsy. We report a case of a 4-year-old boy initially misdiagnosed with facial PWS following ineffective photodynamic therapy. Digital images with quantitive readings acquired by infrared thermography (IRT) camera detected localized hyperthermia within the lesion, indicative of underlying hemodynamic anomalies. Skin biopsy of the lesion was performed and a somatic KARS mutation (p. Gln61His) was detected via targeted sequencing. Subsequent digital subtraction angiography confirmed the presence of micro-arteriovenous fistulas, thereby confirming the diagnosis of early AVM. This case illustrates the clinical utility of IRT in detecting subtle temperature variations associated with vascular pathophysiology. Integrating IRT into initial diagnostic algorithms may enhance the accuracy of differential diagnosis for vascular malformations, particularly early-stage AVMs.